SGRP Annual report 1999 of the CGIAR System-wide Genetic Resources Programme - CGIAR Systemwide Genetic Resources Programme (2000)
SGRP publishes every year a report providing a detailed overview of its activities. This report provides information on activities carried out in 1999.